Shorter, Cheaper, Quicker, Better : Linking Measures of Household Food Security to Nutritional Outcomes in Bangladesh, Nepal, Pakistan, Uganda, and Tanzania - Tiwari, Sailesh; Skoufias, Emmanuel; Sherpa, Maya (World Bank, Washington, DC, 2013)
Using nationally representative household survey data from five countries -- three from South Asia (Bangladesh, Pakistan, and Nepal) and two from Sub-Saharan Africa (Tanzania and Uganda) -- this paper conducts a systematic assessment of the correlation between various measures of household food security and nutritional outcomes of children. The analysis, following the universally accepted and applied definition of food security, is based on some of the most commonly used indicators of food security. The results show that the various measures of household food security do appear to carry significant signals about the nutritional status of children that reside within the household. This result holds even after the analysis controls for a wide array of other socio-economic characteristics of the households that are generally also thought to be associated with the quality of child nutrition. If using these food security indicators as proxy measures for the underlying nutritional status of children is of some interest, then the results show that simple, cost-effective, and easy-to-collect measures, such as the food consumption score or the dietary diversity score, may carry at least as much information as other measures, such as per capita expenditure or the starchy staple ratio, which require longer and costlier surveys with detailed food consumption modules. Across five different countries in South Asia and Africa, the results suggest that the food consumption score, in particular, performs extremely well in comparison with all other measures from the perspective of nutritional targeting as well as for monitoring nutritional outcomes.